Analisis Mengatasi Overblast Analisis Mengatasi Overblas Pada Gardu KA0929 Penyulang Dalung Dengan Metode Uprating Trafo - DWI UTAMA, I GD KURNIA (Jurnal ELIT, 2026)
In the distribution of electrical power, transformers are often overloaded. More load occurs because the number of customers and the electricity needed will increase, therefore the load on the transformer will also increase so that the transformer will experience an overblast. In order for the distribution system to remain stable, the percentage of load on the distribution transformer must not exceed the stipulation, which is 80% of the transformer capacity. The load of the transformer at the distribution substation of KA 0929 Penyulang Dalung at the peak load was 110.6% and was declared overblast. The solution to overcome the overblast transformer at the KA 0929 distribution substation is by uprating the transformer. This study was conducted to analyze the capacity of the transformer needed to overcome the overblast transformer at the distribution substation of KA 0929, which is 250 kVA. The results of the analysis show that after being upgraded, the transformer does not experience interference and the transformer is useful for reducing the capacity of the overblast transformer and lowering the heat temperature in the transformer, so that the quality of electrical energy distribution remains good and improves service to customers.